THEORETICAL AND CONCEPTUAL FOUNDATIONS OF USING INFORMATION SYSTEMS IN THE MECHANISM OF LOCAL GOVERNMENT COMMUNICATION WITH THE PUBLIC - Vovk, Marian (Public Management and Policy, 2025)
The article examines the role of information systems in shaping effective communication between local authorities and citizens in the context of digital transformation. The primary objective of this study is to examine the impact of integrating new information technologies on enhancing the efficiency, transparency, and democratic nature of governance processes at the local level. The article emphasizes the significance of digital platforms, including electronic voting, online petitions, and mobile applications for citizen appeals, as well as other tools that offer new avenues for communication between authorities and the population. This allows improving the improvement of management decisions, responding promptly to the needs of citizens, and increasing the level of public participation in governance processes. The authors emphasize that digital technologies not only reduce bureaucratic barriers but also contribute to the creation of transparent and accessible platforms for interaction, which increases trust in government bodies. The article uses methods of system analysis, comparison, and synthesis, as well as research into the impact of information technologies on the efficiency of governance processes. It was found that the integration of digital technologies into local self-government is a necessary step towards ensuring democracy and accountability of authorities, increasing transparency and quality of public administration. Thanks to the introduction of modern information systems, new communication channels are created that allow citizens to participate more actively in governance processes, as well as influence the support of reforms and the development of democratic institutions at the local level. From the point of view of development prospects, the article considers the great potential of digital technologies for improving governance processes and ensuring more effective models of local governance. However, along with the advantages, digitalization also carries certain risks, such as cyber threats, digital inequality, and information manipulation.